Can occupational therapist-led home environmental assessment prevent falls in older people? A modified cohort randomised controlled trial protocol. Issue 9 (10th September 2018) - Cockayne, Sarah; Pighills, Alison; Adamson, Joy; Fairhurst, Caroline; Drummond, Avril; Hewitt, Catherine; Rodgers, Sara; Ronaldson, Sarah J; Lamb, Sarah E; Crossland, Shelley; Boyes, Sophie; Gilbody, Simon; et al.
Abstract : Introduction: Falls and fall-related injuries are a serious cause of morbidity and cost to society. Environmental hazards are implicated as a major contributor to falls among older people. A recent Cochrane review found an environmental assessment, undertaken by an occupational therapist, to be an effective approach to reducing falls. However, none of the trials included a cost-effectiveness evaluation in the UK setting. This protocol describes a large multicentre trial investigating the clinical and cost-effectiveness of environmental assessment and modification within the home with the aim of preventing falls in older people. Methods and analysis: A two-arm, modified cohort randomised controlled trial, conducted within England, with 1299 community-dwelling participants aged 65 years and above, who are at an increased risk of falls. Participants will be randomised 2:1 to receive either usual care or home assessment and modification. The primary outcome is rate of falls (falls/person/time) over 12 months assessed by monthly patient self-report falls calendars. Secondary self-reported outcome measures include: the proportion of single and multiple fallers, time to first fall over a 12-month period, quality of life (EuroQoL EQ-5D-5L) and health service utilisation at 4, 8 and 12 months. A nested qualitative study will examine the feasibility of providing the intervention and explore barriers, facilitators, workload implications and readiness to employ these interventions into routine practice. An economic evaluation will assess value for money in terms of cost per fall averted. Ethics and dissemination: This study protocol (including the original application and subsequent amendments) received a favourable ethical opinion from National Health Service West of Scotland REC 3. The trial results will be published in peer-reviewed journals and at conference presentations. A summary of the findings will be sent to participants. Trial registration number: ISRCTN22202133 ; Pre-results.